1972
DOI: 10.1139/y72-049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Elastic Properties of Human Intracranial Arteries and Aneurysms

Abstract: Static pressure–volume curves were done on seven intracranial saccular aneurysms and 16 major cerebral arteries from human autopsies. The aneurysms were much less distensible than the arteries. The major change was in the initial or elastin part of the curve (elastance of 6 ± 5 S.D. × 105 dynes/cm per 100% elongation in the artery compared to 13.5 ± 5 × 105 dynes/cm per 100% elongation for the aneurysm; p < 0.005). This agrees well with histological studies which show that elastin is decreased and fragmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 0 publications
3
134
1
Order By: Relevance
“…The magnitude of circumferential strain that we estimated for a luminal pressure change from 30 to 200 mm Hg was 35%, based on the mechanical studies of Scott et al 35 for the larger human brain arteries. Hence, as an example, a muscle layer organized helically at 45° at 30 mm Hg distending pressure would become less helically oriented, to an angle of 36.5° at 200 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of circumferential strain that we estimated for a luminal pressure change from 30 to 200 mm Hg was 35%, based on the mechanical studies of Scott et al 35 for the larger human brain arteries. Hence, as an example, a muscle layer organized helically at 45° at 30 mm Hg distending pressure would become less helically oriented, to an angle of 36.5° at 200 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that a primary subendothelial layer is laid down, due to smooth muscle migration through fenestrations in the internal elastic lamina, 13 with a mainly longitudinal orientation 35 associated by contact guidance and cyclical stretching of the vessel by pulsation of blood pressure in vivo. 39 After migration to the subendothelial layer, the smooth muscle may become primarily a synthesizing cell for connective tissue, 43 generating type HI collagen in the early atherosclerotic process and subsequently type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies consistently report variations in wall thickness between aneurysms and within single aneurysms, and most report that the wall is thinnest in the dome. [12][13][14][15] Histological studies of aneurysms resected during surgery, 12,15 and autopsy-studies of unruptured aneurysms 13,14 were identified, and the reported thicknesses varied between 16 and 400 m. In summary, the reviewed studies indicate that most aneurysms have a wall thickness between 30 and 200 m.…”
Section: Literature Review Of Geometric and Materials Parameters And Bmentioning
confidence: 99%
“…13 In vitro studies of aneurysms from autopsy material, resected aneurysms, and model aneurysms from connective tissues have measured different wall properties, such as elastance and breaking strength. 13,14,16 Based on these directly measured properties, different equations describing aneurysm wall properties have been developed. The most accepted model is the nonlinear isotropic material, described by Fung-Type strain energy function and isotrophic nonlinear hyperelastic material.…”
Section: Literature Review Of Geometric and Materials Parameters And Bmentioning
confidence: 99%
“…Most bifurcations of the cerebral vasculature are structurally stable, but a small number develop a weakness that causes the wall to expand outwardly in the region near the flow divider of the branching artery (Austin et al, 1993;MacDonald et al, 2000;Rowe et al, 2003). Some measurements of the macroscopic mechanical properties of cerebral arteries and aneurysms exist (Coulson et al, 2004;Monson et al, 2003Monson et al, , 2005Scott et al, 1972;Steiger, 1990;Tóth et al, 1998Tóth et al, , 2005 and the structural organisation of these tissues is fairly well documented (Canham et al, 1991b(Canham et al, ,a, 1992(Canham et al, , 1996(Canham et al, , 1999Finlay et al, 1991Finlay et al, , 1995Finlay et al, , 1998Hassler, 1972;MacDonald et al, 2000;Rowe et al, 2003;Smith et al, 1981;Whittaker et al, 1988). In the aneurysmal wall, the tunica media and the internal elastic lamina have often disappeared or are severely fragmented (Abruzzo et al, 1998;Sakaki et al, 1997;Stehbens, 1963;Suzuki and Ohara, 1978;Tóth et al, 1998).…”
Section: Introductionmentioning
confidence: 99%